2006
DOI: 10.1093/ejo/cjl046
|View full text |Cite
|
Sign up to set email alerts
|

How do we evaluate the economics of health care?

Abstract: Economic evaluation has become an integral component of health service research in recent years and will no doubt become more influential. As resources are reduced in health services, more questions are likely to be asked on the costs and benefits of new treatments. Questions are also likely to be aimed at treatments that are currently provided. Economics related to health care is complex and numerous methods of economic evaluation exist. Full economic evaluation involves the assessment of both costs and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…These models usually consider a lifetime horizon that is beyond the scope of this analysis. [42,43] Finally, these findings also only apply to highly treatment-experienced patients with a profile similar to the POWER population. In the phase III TITAN trial, which enrolled less treatment-experienced patients, the superior virological response achieved with DRV/r compared with lopinavir/ritonavir-based HAART was not associated with a higher CD4 cell count increase from baseline after 48 weeks of therapy.…”
Section: Discussionmentioning
confidence: 95%
“…These models usually consider a lifetime horizon that is beyond the scope of this analysis. [42,43] Finally, these findings also only apply to highly treatment-experienced patients with a profile similar to the POWER population. In the phase III TITAN trial, which enrolled less treatment-experienced patients, the superior virological response achieved with DRV/r compared with lopinavir/ritonavir-based HAART was not associated with a higher CD4 cell count increase from baseline after 48 weeks of therapy.…”
Section: Discussionmentioning
confidence: 95%
“…In cardiovascular and respiratory diseases, for example, authors have previously reported the cost per cardiovascular event avoided, [41] whereas the cost per additional pain-free day has been calculated in the management of pain, [42] and the cost per additional symptom-free day is a common cost-effectiveness measure for asthma drugs. [43] A similar approach has been used to estimate the incremental drug cost per additional patient with an undetectable plasma HIV-RNA level at 48 weeks for HAART regimens containing DRV/r 600/100 mg bid compared with HAART regimens containing either investigator-selected control PIs or LPV/r 400/100 mg bid, using the 48-week efficacy results of the pooled POWER 1 and 2 trials.…”
Section: Cost-effectiveness Analyses Of Darunavir With Ritonavir At Amentioning
confidence: 99%
“…There are numerous approaches to the assessment of economic impact in the health sector [13][14][15]. Some, such as the Health Impact Assessment approach [16,17], extend beyond economic aspects to deal with broader societal impact, often referred to as socioeconomic impact [18].…”
Section: Introductionmentioning
confidence: 99%